(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Emulgels have emerged as a promising drug delivery system for the delivery of hydrophobic drugs. The objective of the study was to prepare emulgel of Tolnaftate. Intention of the current study is to expand nanoemulgel of tolnaftate as anti-fungal drug. The drug delivery system provides better-permeable delivery of effective moeighty via topical route in controlled and localized manner. Tolnaftate is most useful drug for take care of skin infections on human skin as athlete's foot, jock itch, and ringworm. It is an antifungal that works by preventing the growth of fungus. The nanoemulgels are characterize with a various number of parameters i.e. particle size, poly-dispersity index, drug content, spreadability, in-vitro permeation rate, microbial assay method. antifungal efficacy of develop nanoemulgels.